Math for the Benefit of Society: A New MATLAB-Based Gen-Ed Course. Issue 3 (21st April 2019) - Isihara, Paul; Townsend, Edwin; Ndkezi, Richard; Tully, Kevin
Abstract: Responding to a call for national reform of mathematical education, as well as a college-wide revision of general education (GE) requirements, we describe a new entry-level, GE course focused on the humanitarian utility of mathematics. This includes a detailed overview of how we taught the course using a Humanitarian MATLAB Lab Manual developed collaboratively with undergraduate students within an applied math program. A PRIMUS edition of this manual with complete MATLAB materials for a GE course is included as an Appendix for interested readers. A variety of social justice issues including peace-building after modern civil wars, continued cancer risk after Chernobyl, gang reduction, various dimensions of human trafficking, the use of a tractor and herbicide in subsistence farming, equitable resource distribution during the Syrian refugee crisis, and access to HIV vaccines are included in this special edition of the manual.